FUNGSI DAN NILAI MANTRA DALAM MASYARAKAT BANJAR - Purwanti, Purwanti; Wahyuni, Ian (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
This study focuses on oral traditions that contain local wisdom. Mantra is an oral tradition that lives and develops in a society, especially in Banjar society. This study aims to discover the functions and values of the mantra that exist in the Banjar community. This research is a library research that uses a descriptive qualitative approach. The research data were obtained through the book collection "Mantra Banjar". Data were collected through the observation stage: read, take notes and to add information, researchers also interviewed informants. Then the data were analyzed by stages; the data classification is in accordance with the spell function classification among the Banjar community. Then, proceed with classifying the valuescontained in the mantra performed by the Banjar community. The function of the Banjar mantra among the Banjar community is to educate, entertain, motivate and document (save). Meanwhile, the values of the Banjar mantra among the Banjar community contain elements of value between man and man, man and God, man and nature, and man and himself.